Defining Abnormal Fetal Growth and Perinatal Risk: Population or Customized Standards? - Sarah J Stock; Jenny Myers (PLoS Medicine, 2017)
In January's Guest Editorial, Sarah Stock and Jenny Myers discuss approaches to fetal and neonatal growth assessment.